Knowledge about cervical cancer and awareness about human papillomavirus vaccination among medical students in Jordan - Alsous,Mervat M.; Ali,Ahlam; Al-Azzam,Sayer; Karasneh,Reema; Amawi,Haneen (PeerJ, 2021)
Objectives To assess the knowledge about cervical cancer and HPV infection and the awareness towards and perceived barriers of HPV vaccination amid medical students in Jordan. Methods The present study is a cross-sectional survey that was conducted for a period of three months in the College of Medicine at six different universities in Jordan. Third-year to sixth-year students from these medical colleges in Jordan were invited to participate in the study. Results There were 504 students that took part in the study with 42.3% being males and 57.7% females. The mean knowledge score of students in our survey was 21.4 ± 4.4 out of 34, which was categorized as a moderate level of knowledge regarding cervical cancer and HPV. Only 40.5% knew about the availability of the HPV vaccine in Jordan, and 65.9% accepted the idea that it is necessary to introduce the HPV vaccine for school girls in Jordan. Conclusions This study highlights that there is inadequate knowledge about cervical cancer and its screening among medical students in Jordan. Despite the limited awareness about the HPV vaccine among the study’s participants, there is a favorable opinion towards the introduction of the vaccine for school girls in Jordan. The data provide a benchmark on the level of knowledge about cervical cancer and awareness about HPV, which can be used to formulate an effective awareness program.
Keywords: Cervical cancer; Jordan; Knowledge; Medical students; Human Papillomavirus; Vaccine